Mental Imagery in Clinical Disorders - David G. Pearson (Frontiers Research Topics, 2017)
Mental imagery refers to the mental simulation or recreation of perceptual experience across different sensory modalities. The exploration of mental imagery represents a new and important area within clinical psychology, but arguably one still in its infancy. While mental imagery has featured prominently in recent theoretical accounts of disorders as diverse as post-traumatic stress disorder, phobia, body dysmorphic disorder, mood disorders, and psychosis, there remains an insufficiently strong theoretical and methodological foundation to enable comparison of the role of imagery across such different disorders. The current research topic presents a diverse range of cutting-edge papers focusing on investigating the underlying mechanisms and/or treatment interventions associated with mental imagery in clinical disorders, with the goal of helping establish those common elements most clinically relevant when investigating mental imagery. The research topic comprises fifteen articles drawn from the fields of psychiatry, psychology, and neuroscience. This is a unique collection of articles that combine different perspectives from the field of clinical psychology with more diverse perspectives drawn from the wider literature on mental imagery. The original research studies and theoretical articles presented are organised around four main chapters that cover imagery and eye movements, imagery and craving, imagery and autobiographical memory, and imagery and clinical disorders. We believe that the range of submissions presented in the research topic make a strong contribution to helping establish a theoretical and methodological foundation that can enable the effective study of imagery across different disorders and domains.